2011
DOI: 10.21608/ejap.2011.94072
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Carcass Characteristics of Dumyati, Muscovy, Peking and Sudani Duck Breeds

Abstract: This experiment was conducted on 120 ducks (30 Dumyati, 30 Peking, 30 Muscovy and 30 Sudani ducks). The ducks were fed complete commercial diets, appropriate for respective species. Slaughter and slaughter value estimation were performed at the age of 12 weeks. Analysis of the chemical composition of meat was made on breast and thigh muscles. Cell-mediated immunity was examined by Phytohemagglutinin-P (PHA-P) at 10 weeks of age. The present result showed that Muscovy strain had significantly heavier body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Molar is highest weight The BW4, 7 and 10, A values for body weight which agree with (Omar et al [15]; Nasr et al [4] who stated that Mulard was 4,021 g at the 10 th w of age. But this study disagrees with Hassan et al [7] and Galal et al [16] who mentioned that the Muscovy showed the highest BW. However, fyan et al [17] reported that the Pekin breed is better than Muscovy and Deshi white ducks.…”
Section: Resultscontrasting
confidence: 99%
“…Molar is highest weight The BW4, 7 and 10, A values for body weight which agree with (Omar et al [15]; Nasr et al [4] who stated that Mulard was 4,021 g at the 10 th w of age. But this study disagrees with Hassan et al [7] and Galal et al [16] who mentioned that the Muscovy showed the highest BW. However, fyan et al [17] reported that the Pekin breed is better than Muscovy and Deshi white ducks.…”
Section: Resultscontrasting
confidence: 99%